Об усреднении нелинейных эллиптических задач с неоднородными условиями - Скрыпник, И.И. (Український математичний журнал, 1995)
Розглядається послідовність розв'язків нелінійних еліптичних задач, коли на одній частині межі задаються умови Діріхле, на іншій — умови Неймана. Будується гранична задача. A sequence of solutions of nonlinear elliptic problems is considered in the case where the Dirichlet conditions are given on the one part of the boundary and the Neumann conditions are given on the other part. The boundary-value problem is constructed.